2018
DOI: 10.1371/journal.pone.0198989
|View full text |Cite
|
Sign up to set email alerts
|

The perception of territory and personal space invasion among hospitalized patients

Abstract: Objectives1) To identify the patient’s perception of invasion of territorial and personal space and 2) to evaluate whether personal characteristics, housing conditions and characteristics of the hospital unit affect this perception.MethodsAnalytical, cross-sectional and quantitative study. An adapted version of the “Anxiety Due to Territory and Space Intrusion Questionnaire” was applied with patients hospitalized in the internal medicine and maternity wards and in the ward for patients with private health insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Intimate space, the area immediately surrounding our bodies (0 to 1.5 feet) is reserved for parents, children, lovers, spouses, and partners. Although breaching this space can bring comfort, especially when words fail (Hans and Hans 2015), it can be counterproductive if patients perceive a lack of control over their own body (Marin, Gasparino, Puggina 2018). It may also be annoying or frightening in some circumstances (Hall 1963; Hans and Hans 2015).…”
Section: How Clinicians Communicatementioning
confidence: 99%
“…Intimate space, the area immediately surrounding our bodies (0 to 1.5 feet) is reserved for parents, children, lovers, spouses, and partners. Although breaching this space can bring comfort, especially when words fail (Hans and Hans 2015), it can be counterproductive if patients perceive a lack of control over their own body (Marin, Gasparino, Puggina 2018). It may also be annoying or frightening in some circumstances (Hall 1963; Hans and Hans 2015).…”
Section: How Clinicians Communicatementioning
confidence: 99%
“…46 47 Professional development should also promote strategies that ensure patients' privacy, not only of their personal and health information, 48 since a leak can undermine the reputation of a health facility, as patients bring to the hospital expectations of receive security, respect, dignity, information and care. 49 Touching patients' personal objects or moving them can be perceived as an invasion of territory and privacy, causing discomfort, 50 reinforcing the need to provide information about privacy and confidentiality before and during hospitalisation. 51 A Greek study showed that patients had little idea of their rights 52 and nursing has a very important role in disseminating this knowledge and ethical principles, establishing a relationship of respect for patients' rights and privacy.…”
Section: Open Accessmentioning
confidence: 99%
“…However, privacy-conscious words and actions can vary depending on the situation in which the nurse is placed, and furthermore, they rely heavily on judgment based on the nurse's personal values and experience. Therefore, depending on the nurse's actions, patients may perceive that their privacy has been violated [8] [9]. Privacy-conscious nursing practice is required, given that the privacy of patients and their families admitted to NICU and GCU can be easily violated by the open floors environment and the words and actions of nurses.…”
Section: Introductionmentioning
confidence: 99%